Bloch wave buckling analysis of axially loaded periodic cylindrical shells. (December 2016) - Ning, Xin; Pellegrino, Sergio
Highlights: An efficient and accurate method for buckling analysis of axially loaded periodic cylindrical shells is presented. This method incorporates the advantages of the Bloch wave method and the stiffness matrix method. This method does not require any smearing, homogenization, or approximation. This method does not require specific-purpose elements and is developed in the environment of Abaqus. Abstract: This paper presents an efficient computational method for predicting the onset of buckling of axially loaded, corrugated or stiffened cylindrical shells. This method is a modification of the Bloch wave method which builds on the stiffness matrix method. A numerical method and an efficient algorithm have been developed to implement the proposed method in the commercial finite element package Abaqus. Numerical examples have shown that, compared to the nonlinear buckling analyses based on detailed full finite element models, the proposed method can obtain highly accurate buckling loads and buckling modes and can achieve very significant reductions in computational time.